The Relationship of Demographical Factors on University Students' Coping Strategy - Aprezo Pardodi Maba (IAI Ma'arif NUMetro Lampung, 2023)
This study examined the relationship between demographical factors and coping strategies in university students. A sample of 606 students from a large public university in the Indonesia completed an online survey that included measures of demographical factors (such as gender, age, living area, siblings, spending in a month, part-time job, and living arrangement) and coping strategies. The results of the study indicated that having a part-time job was significantly correlated with coping strategies overall, as well as with problem-focused coping and emotion-focused coping in particular. Other demographical factors, such as gender, age, living area, siblings, spending in a month, and living arrangement, were not found to be significantly correlated with coping strategies. These findings have important implications for understanding the ways in which demographical factors influence coping strategies in university students and may inform the development of targeted interventions to support the mental health and well-being of university students. Future research could consider using a more diverse sample and a longitudinal design to more fully understand the complex relationships between demographical factors and coping strategies in university students. Keywords: Demographical Factors, Coping Strategies, Mental Health